Analysis of green marketing, green brand image, green perceived value, and environmental knowledge on green purchase decision at The Body Shop customers in Jabodetabek - Juliana, Siska; Sijabat, Rosdiana (Enrichment : Journal of Management, 2023)
The increasing amount of waste generated from the use of cosmetic products makes people pay more attention to their purchasing decisions. This study aims to test and analyze the effect of green marketing, green brand image, green perceived value, and environmental knowledge on green green purchase decisions for The Body Shop customers in JABODETABEK. This study uses primary data collected from 150 respondents of The Body Shop customers in JABODETABEK. The construction of the relationship model in this research was tested with partial least square-structural equation modeling (PLS-SEM) with the Smart PLS 3.2.9 program. The results showed that green marketing has a positive and significant effect on green brand image, green brand image has insignificant effect on green purchase decision, green marketing has a significant positive effect on green perceived value, green perceived value has a significant positive effect on green purchase decision, green marketing has a significant positive effect on green purchase decision, and environmental knowledge plays a significant role in mediating the effect of green marketing on purchase decision. This model can also be used by other environmentally friendly cosmetic companies in developing marketing strategies to increase customer green purchase decisions